1987
DOI: 10.1017/s0022029900025632
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies on nucleotide sequences encoding the caseins

Abstract: Introduction Methodology Casein cDNA sequences The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Analysis of the patterns of inheritance of these allelic variants, together with those of the other caseins, indicates that the genes for all four caseins occur as a tightly linked cluster [6,71. Analysis of the bovine casein genes as the cDNA level, as well as of their homologues in other species, reviewed in [8], has confirmed that the genes for the three calcium-sensitive caseins are evolutionarily related and constitute a small gene family. It appears that the ti-casein gene, although linked to the other casein genes, is unrelated to them.…”
mentioning
confidence: 92%
“…Analysis of the patterns of inheritance of these allelic variants, together with those of the other caseins, indicates that the genes for all four caseins occur as a tightly linked cluster [6,71. Analysis of the bovine casein genes as the cDNA level, as well as of their homologues in other species, reviewed in [8], has confirmed that the genes for the three calcium-sensitive caseins are evolutionarily related and constitute a small gene family. It appears that the ti-casein gene, although linked to the other casein genes, is unrelated to them.…”
mentioning
confidence: 92%
“…Caseins appear to be a rapidly evolving gene family, presumably due to the minimal structural requirements for function (Bonsing and Mackinlay, 1987). However, in contrast to the calcium-sensitive α s1 -, β-, and α s2 -caseins, the κ-casein fraction plays a crucial role in the formation, stabilization, and aggregation of the casein micelles and thus affects the technological (Mariani et al, 1976;Aleandri et al, 1990;Lodes et al, 1996;Falaki et al, 1997) and nutritional properties of milk (Mercier et al, 1973(Mercier et al, , 1976Malkoski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences of the casein genes are poorly conserved during evolution (2,3,28). Of all of the caseins, -casein is the most conserved in terms of its molecular architecture.…”
Section: Discussionmentioning
confidence: 99%